Evaluation of Processing and Storage Techniques for Cat’s Whiskers (Orthosiphon aristatus) Leaves in Tana Toraja to Improve the Quality and Shelf Life of Herbal Tea Products - Golindira Randa; Elianus Samben (Program Studi Pendidikan Biologi FKIP Unpatti, 2026)
The utilization of cat’s whiskers (Orthosiphon aristatus) as a herbal plant has long been an integral part of the cultural and traditional health practices of the Tana Toraja community. This medicinal plant has been widely used to treat various ailments, particularly urinary tract disorders, and its use has been passed down through generations. However, these traditional practices have not yet been supported by systematic efforts to improve product quality and added value. This study aims (1) to evaluate the effectiveness of different processing techniques for cat’s whiskers leaves on the quality of ready-to-brew herbal tea, and (2) to examine the influence of storage techniques on the quality and shelf-life of cat’s whiskers herbal tea. A Completely Randomized Design (CRD) was employed, consisting of three processing methods (air-dried sample; blanched and oven-dried at 60°C; and unblanched sample oven-dried at 60°C), two types of packaging (glass jar and standing pouch zipper seal), and two storage conditions (room temperature and cold storage). Observed parameters included moisture content, infusion pH, dried leaf color, and infusion color at weeks two and four. ANOVA results indicated that processing, packaging, and storage had significant effects on moisture content and color (α < 0.05), but no significant effect on infusion pH. The treatment involving blanching and oven-drying at 60°C with airtight packaging and cold storage (P2K2S2) produced the best quality, characterized by low moisture content (6.8–8.7%) and the highest color stability. The pH remained stable (6.20–6.92) throughout the storage period. Based on these findings, it is concluded that controlled drying, airtight packaging, and low-temperature storage are the most effective combination of treatments to enhance the quality and shelf-life of cat’s whiskers herbal tea.